2013
DOI: 10.1007/s00134-013-3122-6
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to validate the modification of the American-European consensus definition of acute lung injury/acute respiratory distress syndrome by the Berlin definition in a university hospital

Abstract: The present study did not validate the Berlin definition of ARDS. Neither the stratification by severity nor the PaO2/FiO2 at study entry was independently associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 30 publications
3
83
1
2
Order By: Relevance
“…Villar et al 9 reported that mortality was better described by assignment of the ARDS criteria (in terms of P/F ratio) at a given positive end-expiratory pressure (PEEP) and Fio 2 at 24 hours. Hernu et al, 10 in a prospective survey, did not fi nd any difference in mortality between patients with mild versus moderate ARDS.…”
mentioning
confidence: 88%
“…Villar et al 9 reported that mortality was better described by assignment of the ARDS criteria (in terms of P/F ratio) at a given positive end-expiratory pressure (PEEP) and Fio 2 at 24 hours. Hernu et al, 10 in a prospective survey, did not fi nd any difference in mortality between patients with mild versus moderate ARDS.…”
mentioning
confidence: 88%
“…There are no data that link a particular baseline PaO 2 /FiO 2 to predictable structural changes in the alveolar-capillary membrane. Two recent studies [14,15] showed that the use of non-standardized baseline PaO 2 /FiO 2 were incapable of separating patients into distinct categories of severity with significantly different mortalities. An autopsy study revealed that the Berlin criteria did not correlate with the presence of diffuse alveolar damage in more than 50 % of patients categorized as moderate and severe ARDS [16].…”
Section: Searching For a Satisfactory Ards Definitionmentioning
confidence: 99%
“…ARDS is also classified as mild, moderate or severe, according to PaO 2 /FiO 2 following ventilation with a minimal PEEP of 5 cmH 2 O (19). Each stage has been demonstrated to be associated with different mortality rates, i.e., around 27-29% in mild, 32-35% in moderate and 42-45% in severe ARDS (8,19) 20).…”
Section: Introductionmentioning
confidence: 99%